Puberty and physical self-perceptions of competitive female figure skaters II: Maturational timing, skating context, and ability status - Monsma, E. V. (Research Quarterly for Exercise and Sport, 2008)
Aesthetic sports such as figure skating are characterized as early entry in which participation begins as young as 5 years of age and specialization occurs as early as 8 years of age. The concurrent development of talent and the body under the scrutiny of judges (i.e., subjective evaluation especially involved in presentation scoring), coaches, and sport officials may be especially stressful for young girls. Increases in physical size are seen as a liability to biomechanics and possibly the presentation component the sport. Surprisingly, limited research has considered the relationship between puberty and psychological characteristics of young athletes. One study of figure skaters found that menarcheal status was a stronger predictor than age in explaining the variance in their self-perceptions. Postmenarcheal skaters had significantly lower self-esteem and physical self-concept and were less satisfied with their appearance than premenarcheal skaters. Surprisingly, skating context (i.e., skating with a partner) was not a significant correlate of the self-perceptions. Further examination of puberty and skating context on physical self-perceptions in aesthetic sports was recommended (Monsma, Malina, & Feltz, 2006).